Increased Expression of the Matrix-Modifying Enzyme Lysyl Oxidase-Like 2 in Aggressive Hepatocellular Carcinoma with Poor Prognosis - Choi, Jiwoon; Chung, Taek; Rhee, Hyungjin; Kim, Young-Joo; Jeon, Youngsic; Yoo, Jeong Eun; Noh, Songmi; Han, Dai Hoon; Park, Young Nyun (EDITORIAL OFFICE GUT & LIVER, 2019)
Background/Aims: Lysyl oxidase-like 2 (LOXL2), a collagen-modifying enzyme, has been implicated in cancer invasiveness and metastasis. Methods: We evaluated the expression of LOXL2 protein, in addition to carbonic anhydrase IX (CAIX), keratin 19, epithelial cell adhesion molecule, and interleukin 6, in 105 resected hepatocellular carcinomas (HCCs) by immunohistochemistry. Results: LOXL2 positivity was found in 14.3% (15/105) of HCCs, and it was significantly associated with high serum alpha-fetoprotein levels, poor differentiation, fibrous stroma, portal vein invasion, and advanced TNM stage (p<0.05 for all). Additionally, LOXL2 positivity was significantly associated with CAIX (p=0.005) and stromal interleukin 6 expression (p=0.001). Survival analysis of 99 HCC patients revealed LOXL2 positivity to be a poor prognostic factor; its prognostic impact appeared in progressed HCCs. Furthermore, LOXL2 positivity was shown to be an independent predictor of overall survival and disease-specific survival (p<0.05 for all). Interestingly, co-expression of LOXL2 and CAIX was also an independent predictor for overall survival, disease-specific survival, disease-free survival, and extrahepatic recurrence-free survival (p<0.05 for all). Conclusions: LOXL2 expression represents a subgroup of HCCs with more aggressive behavior and is suggested to be a poor prognostic marker in HCC patients.
Keywords: INVASIVE BREAST-CARCINOMA; CARBONIC-ANHYDRASE-IX; EXTRACELLULAR-MATRIX; MOLECULAR ROLE; HYPOXIA; LOXL2; STEMNESS; MARKER; METASTASIS; PROGRESSION